Associations between lymphovascular space invasion, nodal recurrence, and survival in patients with surgical stage I endometrioid endometrial adenocarcinoma - Ashley E. Veade; Jonathan Foote; Jessie Ehrisman; Gloria Broadwater; Brittany A. Davidson; Paula S. Lee; Angeles Alvarez Secord; Andrew Berchuck; Laura J. Havrilesky (World Journal of Surgical Oncology, 2019)
Abstract Objective To investigate the predictive value of lymphovascular space invasion (LVSI) for nodal recurrence and overall survival (OS) in patients with stage I endometrioid endometrial cancer (EC) following surgical staging that included adequate lymph node sampling. Methods Retrospective analyses of patients undergoing surgical staging for FIGO stage I endometrioid EC between 1998 and 2015 were performed using an institutional database and the National Cancer Database (NCDB). Using the institutional database, logistic regression modeling identified predictors of nodal recurrence; Cox proportional hazards modeling was used to predict progression-free survival (PFS). Utilizing NCDB, Cox proportional hazards modeling was used to predict OS. The Kaplan-Meier method was used to estimate hazard ratios (HR). Survival curves were compared using the log-rank test. Results Among 275 institutional cases, LVSI was present in 48 (17.5%). There were 11 nodal recurrences: 18.8% (9/48) of cases with LVSI had a nodal recurrence compared to 0.88% (2/227) of those without LVSI. In multivariate analysis of institutional data, LVSI was the only significant predictor of nodal recurrence (p = 0.002). Among 28,076 NCDB cases, LVSI was present in 3766 (13.5%). In multivariate analysis of NCDB, grade 3, LVSI, and depth of invasion (all p <  0.001) were prognostic for OS after adjusting for adjuvant radiation. Conclusion LVSI is an independent prognostic factor for nodal recurrence in stage I endometrial cancer with lymph node assessment. LVSI is associated with lower OS in NCDB. Given these findings, adjuvant therapy could be considered in these patients.